Integrated Analysis of Molybdenum Nutrition and Nitrate Metabolism in Strawberry - Liu, Li; Shi, Hongmei; Li, Shaoxuan; Sun, Mingyue; Zhang, Rui; Wang, Yongmei; Ren, Fengshan (Frontiers in Plant Science, 2020)
Molybdenum (Mo) is a component of the Mo cofactor (Moco) of nitrate reductase (NR) and is therefore essential for nitrate metabolism. However, little is known about Mo deficiency phenotypes or about how physiological and molecular mechanisms of Mo uptake and transport influence nitrate uptake and utilization in strawberry. Here, we used physiological and cytological techniques to identify Mo deficiency phenotypes in strawberry. Seedlings cultured with MoO42- grew well and exhibited normal microstructure and ultrastructure of leaves and roots. By contrast, seedlings cultivated under Mo-deficient conditions showed yellow leaf blades and ultrastructural changes such as irregular chloroplasts and unclear membrane structures that were similar to the symptoms of nitrogen deficiency. We cloned and analyzed a putative molybdate transporter, FaMOT1, which may encode a molybdate transporter involved in the uptake and translocation of molybdate. Interestingly, the addition of the molybdate analog tungstate led to lower tissue Mo concentrations, reduced the translocation of Mo from roots to shoots, and increased the plants’ sensitivity to Mo deficiency. Seedlings cultivated with MoO42- altered expression of genes in Moco biosynthesis. As expected, NR activity was higher under sufficient MoO42- levels. Furthermore, seedlings grown on Mo-deficient medium exhibited decreased 15NO3- translocation and lower 15NO3- use efficiency. These findings represent an important step towards understanding how molybdate transport, concentration, and deficiency symptoms influence nitrate uptake and utilization in strawberry.